Successful treatment of lower eyelid epiblepharon by injection of botulinum toxin A in patients under two years of age - Chen, CY; Nava-Castaneda, Angel (Nepalese Journal of Ophthalmology, 2013)
Introduction: Epiblepharon is characterized by a cutaneous horizontal fold adjacent to the lid margin. Some cases showed spontaneous resolution, others required surgical treatment. We propose a medical treatment with botulinum toxin type A (BTX-A). Objective: To provide clinical evidence of the usefulness of botulinum toxin type A (BTX-A) in patients with lower eyelid epiblepharon. Subjects and methods: This was a prospective, non-randomized, nonmasked study. Patients with lower eyelid epiblepharon with corneal eyelash contact were included in the study. The scale proposed by Khwarg & Lee (1997) was used to assess the epiblepharon clinical evaluation. A single dose of 12.5 IU of BTX-A (Dysport ®) was directly injected into the medial pre-tarsal orbicularis muscle region in the lower eyelid. Patients were evaluated before the injection and at 1, 4, 12 and 24 weeks after the injection. We performed descriptive statistics and Wilcoxon Signed Rank Test, comparing prior injection measurements to post injection measurements at the 24th week. A p < 0.05 was considered statistically significant. Each eye was separately analyzed. Results: Fourteen eyes of seven Hispanic patients were treated, five female and two male. The mean age was 8.4 months (4 - 14 months). The height of the skin-fold, the area of the cornea touched by the cilia and the symptoms score improved after the first week of BTX-A injection and remained so until the end of study (p < 0.05). No major complications were noted. Conclusion: The effect of a single 12.5 IU injection of BTX-A (Dysport ®) into the medial orbicularis muscle portion in the lower eyelid epiblepharon patients successfully improves the clinical signs and symptoms. Nepal J Ophthalmol 2013; 5(10): 177-181 DOI: http://dx.doi.org/10.3126/nepjoph.v5i2.8709